Pengaruh Pengetahuan Etika Terhadap Persepsi Etis Mahasiswa Akuntansi Dengan Love Of Money Sebagai Variabel Intervening (Studi Kasus Mahasiswa Program Studi Akuntansi di Lima Perguruan Tinggi Daerah Istimewa Yogyakarta) - Sri Ayem; Loja Dian Evi Leni (Universitas Kristen Maranatha, 2020)
This study aims to examine the effect of ethical knowledge, internship experience, and economic status on the ethical perceptions of accounting students with love of money as an intervening variable. The data used are primary data. The method used is multiple analysis. The sampling technique used in this study was convenience sampling and 90 data samples were obtained. The results of this study indicate that the ethical knowledge variable has a positive effect on the ethical perceptions of accounting students, while ethical knowledge has a negative effect on love of money. love of money has a negative effect on the ethical perceptions of accounting students. Ethical knowledge negatively affects the ethical perceptions of accounting students through love of money as an intervening variable. Keywords : Ethical Knowledge, Ethical Perception, Accounting Student, Love of Money